Indonesia health care system and Asean economic community - Gunawan, Joko; Aungsuroch, Yupin (International Journal of Research in Medical Sciences, 2017)
ASEAN Economic Community (AEC) is a trend issue among ten member countries, including Indonesia. AEC is expected to bring ten member countries close together. To the success of AEC, Indonesia has a role in promoting trade areas and service across boundaries. However, the profile of the countries is needed in order to learn, work, and collaborate among member countries. Therefore, this paper aims to describe Indonesian country, its health system, the production and distribution of health professionals, and some concerns related to AEC. Indonesia, with its population of over 250 million, has health problems and challenges related to health care system. Nowadays, Indonesia is in the process of effective decentralization and in the effort of achieving Universal Health Coverage. Indonesia has made some progress in increasing the life expectancy, and the maternal and infant mortality rate is dropped compared to previous years. In improving healthcare service, Indonesia has been increased the number of health professionals to meet the growth demand. However, the gap of number of physician and nurses still exist. Unequal distribution and shortage of physician and nurses are the major concerns, including the surplus of nurses. Indonesian government proposes the program of worker contract scheme or Pegawai Tidak Tetap (PTT) to solve unequal distribution of health professionals, and provide the program for nurse mobility to migrate to other countries such as Japan, United Emirate Arab (UEA), Kuwait, the Netherlands, Great Britain, Brunei, and other Middle East countries to decrease the number of surplus. However, AEC, by looking at this challenges, is expected to improve health care system and service in Indonesia, and close the gap by collaborating among ten ASEAN member countries through 4 modes of AEC consisting of cross border supply, consumption abroad, commercial presence, and movement of natural persons.